Cendawan entomopatogen sebagai penginduksi ketahanan tanaman: Sebuah tinjauan sistematis: Entomopathogenic fungi as plant resistance inducer: A systematic review - Vajri, Indri Yanil; Trizelia, Trizelia; Kuswardani, Retna Astuti; Saragih, Magdalena (Jurnal Entomologi Indonesia, 2024)
IInsect pathologists' attention to the potential of entomopathogenic fungi (EPF) as inducers of plant resistance has increased in recent years. Several types of EPF that have received attention as biocontrol agents for insect pest populations include Beauveria bassiana, Metarhizium anisopliae and Trichoderma sp. because they are able to infect and kill insects directly, has a wide host range, and has been used to control various types of insect pests. Apart from being able to infect and kill insect pests, EPF can also live endophytically in plant tissue and increase plant resistance to pest attacks. The presence of EPF as endophytes is able to induce plant resistance by stimulating an increase phytohormones production. In this article, we reviewed the role of fungi as entomopathogens, the characteristics of entomopathogenic fungi, and their role as inducers of plant resistance. The review was carried out by collecting information  from original articles and related reports which reviewed the results of research on the role of entomopathogenic fungi as plant resistance inducers by including the keywords entomopathogenic endophytic fungi, resistance induction, characterization, systemic resistance and herbivorous insects. This systematic review concludes that EPF as an inducer of plant resistance is a very promising control alternative in the development of plant protection management against insect pests.